2011
DOI: 10.1177/1043986211425725
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Race on the Police Decision to Search During a Traffic Stop

Abstract: Racial profiling is an important issue in contemporary policing. Research in this area, especially in the decision to search, has relied on an outcomes test and correlates that are largely devoid of theory. Thus, the research is unable to provide a clear understanding of police decision making during a traffic stop. The purpose of the present study was to examine this process. Using data from more than 36,000 traffic stops from Louisville, KY, the present study applies the focal concerns theory to this decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Some studies have examined whether the citizen involved in OPENING THE BLACK BOX OF OFFICER DECISION-MAKING 967 a police-citizen encounter was "known to police" 2 (Engel & Silver, 2001; also see Vito & Walsh, 2008) for a comparison of officer action in cases where the citizen was known vs. stopped), the reputation of the citizen 3 (i.e. whether the police believe the suspect has a criminal record, is carrying a weapon, will be assaultive, or is a gang member) , and whether a records check was initiated by the police (Alpert et al, 2005Higgins, Vito, & Grossi, 2012;M. Smith et al, 2006).…”
Section: Stability In Behavior and Criminal Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have examined whether the citizen involved in OPENING THE BLACK BOX OF OFFICER DECISION-MAKING 967 a police-citizen encounter was "known to police" 2 (Engel & Silver, 2001; also see Vito & Walsh, 2008) for a comparison of officer action in cases where the citizen was known vs. stopped), the reputation of the citizen 3 (i.e. whether the police believe the suspect has a criminal record, is carrying a weapon, will be assaultive, or is a gang member) , and whether a records check was initiated by the police (Alpert et al, 2005Higgins, Vito, & Grossi, 2012;M. Smith et al, 2006).…”
Section: Stability In Behavior and Criminal Historymentioning
confidence: 99%
“…Results from these studies are mixed on the relationship between these variables and police behavior. For example, Alpert et al (2005) found no increase in traffic stops of minority citizens subjected to a records check, Higgins et al (2012) found no effect of records checks on the likelihood of a consent search, and Garner et al (2002) reported reduced use of force rates when the suspect was believed to be possess a gang affiliation. Conversely, Engel and Silver (2001) reported higher rates of arrest for individuals "known to the police," Gottfredson and Gottfredson (1988) indicated that suspects with a criminal record were more likely to be arrested, and M. Smith et al (2006) found arrest to be more likely if a records check was conducted on the citizen, but reported the relationship between minority citizens and arrest diminished once record checks were considered.…”
Section: Stability In Behavior and Criminal Historymentioning
confidence: 99%
“…Despite claims about discrimination against Since Lamberth's studies, the research on ethnic profiling has been extensive. Researchers have been examining the reasons for profiling, public perceptions of profiling, its consequences, procedural aspects, and ways of dealing with it (see, for example, Ioimo et al 2007;Liederbach et al 2007;Gilliard-Matthews, Kowalski, and Lundman 2008; Barnum and Perfetti 2010;Tillyer, Klahm IV, and Engel 2011;Higgins, Vito, and Grossi 2011;Lundman 2012;Tillyer and Engel 2013). For the most part, research was conducted in the field of traffic safety, apparently because of the availability of data.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed city residents receive less enforcement action (Higgins et al, 2012;Novak, 2004), but other research revealed residents receive more enforcement (Ingram, 2007;Rojek et al, 2012). The results from the current study suggest city residents have increased odds of receiving multiple citations.…”
Section: Discussionmentioning
confidence: 98%
“…The theory argues there are three components of the decision making process: blameworthiness, protection of the community, and practical constraints and consequences (Steffensmeir, Ulmer, & Kramer, 1998). Higgins, Vito, and Grossi (2012) The research question examined in this study is "what are the differences in the odds of receiving multiple citations during a traffic stop when examining the ethnic dyad between the motorist and officer?" The question generates the following hypotheses derived from the tenets of focal concern and social conditioning theories:…”
Section: And Mostmentioning
confidence: 99%